PENDAMPINGAN EKONOMI KERTHI BALI MELALUI PROGRAM BANGKITKAN BALIKU - Gandiwo Sri Mahatmo; Juniati Gunawan; I Putu Fery Karyada; Arty Dwi Januari (UNHI Press, 2023)
This program aims to assist and evaluate the implementation of the Kerthi Bali economy. There are several steps start from planning, programming, evaluating the Kerthi Bali economy, and reporting. Based on the results of this community service program, the Kerthi Bali economic implementation policy has had a positive impact on the development of Balinese nature, culture and people through the program's leading sectors. Local values and products have raised their dignity and quality to compete on a national and international scale. To have more sustainable impact on the implementation of the Kerthi Bali economy, the Pentahelix collaboration through the Awaken Baliku Program is appropriate. There is a role for the Government, Academics, Corporations, Society and Media in implementing Kerthi Bali's Economic programs.